1983
DOI: 10.2527/jas1983.574807x
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Performance of Gyr Cows: The Effect of Weaning Age of Calves and Postpartum Energy Intake

Abstract: Two nutritional levels following parturition and five weaning ages for the calf were evaluated to study their effect of reproduction in Gyr cows in the savannas of West Central Brazil (Campos Cerrados). Early weaning of calves reduced postpartum weight losses and shortened the postpartum interval to conception. Energy level did not affect cow weight at weaning or conception, the number of days from parturition to first estrus or the number of matings/conception; however, the postpartum period to conception was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
4

Year Published

1987
1987
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 11 publications
1
5
0
4
Order By: Relevance
“…O desmame aos 90 dias ou menos de idade tem resultado no aumento da taxa de reprodução, conforme constatado por vários autores (Moore & Rocha, 1983;Lobato & Barcellos, 1992;Moojen et al, 1994;Moletta & Perotto, 1997;Restle et al, 2001).…”
Section: Introductionunclassified
“…O desmame aos 90 dias ou menos de idade tem resultado no aumento da taxa de reprodução, conforme constatado por vários autores (Moore & Rocha, 1983;Lobato & Barcellos, 1992;Moojen et al, 1994;Moletta & Perotto, 1997;Restle et al, 2001).…”
Section: Introductionunclassified
“…Early weaning is known to enhance reproductive performance of underfed beef cows (Moore and da Rocha 1983;Holroyd et al 1990;Schlink et al 1994;Coppo et al 2002;Arthington et al 2004), an effect shown also in Table 6 that demonstrates the trade-offs between weaning age and LWs of calves, LWs of their dams and intercalving intervals. Moore and da Rocha (1983) investigated the effects of 2 levels of nutrition and 5 weaning ages in Zebu Gyr breed cows fed hay of B. decumbens in the Brazilian Cerrados and found that, irrespective of the cows' nutritional level, early weaning of calves improved cow weights at different stages throughout the reproductive cycle and subsequent reproductive performance.…”
Section: Discussionmentioning
confidence: 98%
“…Weights of cows at weaning were 313 kg and 325 kg on low and high supplementary energy treatments, respectively, and the authors suggested that Zebu cows rarely conceive if suckling cows weigh less than 300 kg. Weights of cows at weaning decreased linearly from 352 kg, when calves were weaned at 1 month of age, to 294 kg if calves were weaned at 6 months of age, with LW losses during lactation increasing from 21 to 102 kg for the respective weaning ages (Moore and da Rocha 1983). Mukasa-Mugerwa (1989) reviewed the literature regarding reproduction of Zebu cattle in the tropics, and noted that tropical cattle dependent on natural pastures most often calve in alternate years, but animals with access to good quality sown pastures have improved reproductive performance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations